2019
DOI: 10.1007/s00382-019-04735-y
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Arctic freshwater content and transport to model resolution

Abstract: We compare the representation of the Arctic liquid and solid freshwater volumes, and their transports to/from the Arctic, using simulations with different ocean and atmosphere model resolutions from models participating in the EU H2020 PRI-MAVERA project. Regarding ocean resolution, we find less liquid freshwater in the central Arctic Ocean and more in the Kara and Laptev seas in the model simulations at higher resolution compared with the model simulations at lower resolution. The mean sea ice thickness does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
8
1
1
Order By: Relevance
“…We do not find any resolution dependency of the correlation between freshwater exports and convection in the Labrador Sea. This result is in contrast to a recent study from Fuentes Franco and Koenigk (2019) where they analyzed a set of HadGEM3-GC2 simulations at different resolutions and found larger correlations with increased resolution. non-eddying to eddy-present and eddy-rich".…”
Section: The Impact Of Arctic Freshwater and Sea Ice Exports On The Variability Of Deep Convectioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We do not find any resolution dependency of the correlation between freshwater exports and convection in the Labrador Sea. This result is in contrast to a recent study from Fuentes Franco and Koenigk (2019) where they analyzed a set of HadGEM3-GC2 simulations at different resolutions and found larger correlations with increased resolution. non-eddying to eddy-present and eddy-rich".…”
Section: The Impact Of Arctic Freshwater and Sea Ice Exports On The Variability Of Deep Convectioncontrasting
confidence: 99%
“…Recent studies found that the increased resolution in the HighResMIP models improved many aspects of the ocean including temperature and salinity biases (Gutjahr et al 2019), the northward ocean heat transport (Grist et al 2018), sea ice in the Atlantic sector of the Arctic Ocean (Docquier et al 2019(Docquier et al , 2020, the position of the North Atlantic Current (Sein et al 2018) as well as Arctic freshwater exports (Fuentes Franco and Koenigk 2019), all of them with the potential to improve the representation of Labrador Sea convection.…”
Section: Introductionmentioning
confidence: 99%
“…The liquid FWC calculation quantifies the vertically integrated salinity anomaly from a particular reference salinity (Sref), which in this case is 34.8 psu indicated by the mean of the Arctic Ocean and commonly used in other studies [7][8][9]. Following Carmack et al [10], Fuentes-Franco et al [11], and Dewey et al [12], we calculate integrated liquid FWC (m) from salinity measurements and estimations using the equation:…”
Section: Observations and Modelsmentioning
confidence: 99%
“…The third type of error resides in the deficiency of CMIP models to physically describe the dynamical processes in the Arctic Ocean. For example, model resolution can impact the spatial pattern of liquid freshwater in the Arctic Ocean (Fuentes‐Franco & Koenigk, 2019; Q. Wang, Wekerle, Danilov, Wang, & Jung, 2018). Model uncertainty could be also due to important yet missing processes in the model.…”
Section: Discussionmentioning
confidence: 99%